The Case Against Separation of Current Operating Profit and Holding Gain. - Prakash, Prem; Sunder, Shyam (The Accounting Review, 1979)
ABSTRACT: Claims about the benefits to be derived from dichotomizing income into current operating profit (COP) and holding gain (HG) are examined in this article. Separability of an asset from the risk of change in its price is shown to be a necessary and sufficient condition for separate evaluation of the operating and holding decisions with respect to the asset. When risk is separable, the appropriate breakdown of income into operating and holding components is defined. When the risk is not separable, no meaningful breakdown is possible. Other claims for a COP-HG dichotomy, e.g., the usefulness of COP in making various business decisions and interfirm and interperiod comparisons, are shown to be unjustified. In the absence of benefits, the direct cost of compiling data positively unattractive. The arbitrary nature of this dichotomy is illustrated through the construction of an equally defensible alternative.